Arthur v. the rest - Coren, Alan.; Astrop, John (London : Robson, 1981)
How can a pig change the course of history ? What brought about the downfall of Lower Stoatmumbling? Why did W. G. Grace face a team of twenty-two players? How did a village idiot change the game of cricket?
Keywords: Pig -- Fiction